Feasibility of the solar/chlorine treatment for lipid regulator degradation in simulated and real waters: The oxidation chemistry and affecting factors. (July 2019) - Wang, Liping; Fang, Jingyun; Zhang, Xiang; Xu, Xibing; Kong, Xiujuan; Wu, Zihao; Hua, Zhechao; Ren, Ziran; Guo, Kaiheng
Abstract: This work investigated the feasibility and mechanisms of solar/chlorine process in the removal of a kind of emerging contaminants, lipid regulators (gemfibrozil (GFRZ), benzafibrate (BZF), and clofibric acid (CA)), in simulated and real waters. These lipid regulators could be effectively removed by solar/chlorine treatment, and their corresponding pseudo-first-order rate constants ( k ′) increased with increasing chlorine dosage. The degradation of GFRZ and BZF was primarily ascribed to reactive chlorine species (RCS) and ozone, while that of CA was mainly attributable to hydroxyl radical (HO ) and ozone. As pH rose from 5.0 to 8.4, k ozone ′ of GFRZ and BZF increased, while k HO ′ decreased. However, k RCS ′ of GFRZ increased by 130%, while that of BZF decreased by 43.3%. These changes resulted in slight changes in the overall k ′s with increasing pH. k ′s of GFRZ, BZF, and CA by solar/chorine treatment were inhibited by natural organic matter (NOM) while the presence of bromide enhanced the degradation of GFRZ by solar/chlorine process. The degradation of lipid regulators was still effective in a secondary wastewater effluent sample and a sand-filtered water sample, although that was inhibited due to the dissolve organic matter (DOM) contained in real waters. The acute toxicity during the degradation of GFRZ by solar/chlorine treatment was comparable to that by treatment with chlorine alone. This study demonstrated that RCS played an important role in the degradation of micropollutants by the solar/chlorine treatment and the feasibility of solar/chlorine process in the application for the degradation of organic compounds in real waters. Graphical abstract: Image 1 Highlights: Lipid regulators could be effectively degraded by the solar/chlorine treatment. RCS and O3 were predominant reactive species for GFRZ and BZF degradation. The k ′s of GFRZ and BZF were affected by chlorine dosage rather than pH. The acute toxicity in the solar/chlorine process was comparable to that of chlorination alone. The solar/chlorine treatment was also efficient for the removal of lipid regulator in real waters.